MATERNITY PROTECTION OF WOMEN WORKERS: A COMPARATIVE STUDY OF INDONESIAN AND MALAYSIAN LABOR LAWS - Badratun Nafis; Sanusi Bintang (Universitas Syiah Kuala, 2021)
This study analyses the similarities and differences of maternity protection under Indonesia and Malaysia's Labor Law. The method used in this research is a normative and comparative approach. This study shows several differences in maternity protection from both laws, such as the duration of maternity leave and the provision of breastfeeding entitlement. However, few similarities are also found, such as both laws provide social and health protection under the labor law. Malaysian lawmakers should revise the Employment Act 1955, which covers work protection and breastfeeding, and both countries should ratify the Maternity Protection Convention of 2000 to better protect women workers in the workplace.Keywords: Maternity protection, Women worker, International convention, Indonesia and Malaysia labor law.